Objective Function BF-ETX for RPL Routing Protocol (2018)
This paper presents the adaptation and implementation of the objective function in routing protocol RPL (Routing Protocol for Low Power and Lossy Networks) restating in terms of the status of the connection for better performance quality of service offered. In this way, a new routing metric that improves the indicators quality of service was established: network lifetime, packet delivery and energy savings of LLN networks outlined in the framework of the Internet of Things (IoT); all within the functional specifications for these networks of Internet and Engineering Working Group (In English: Internet Engineering Task Force - IETF). It was performed a series of tests and different simulations in Cooja, where BF-ETX generates better results in terms of network latency and power consumption in densely deployed networks and large-scale front MRHOF. This way, it can achieve a better performance of LLNS to large scale in terms of quality of service compared to routing problems.